Sugar Form Product Innovation and Education Packaging and Labeling for the People of Putrapinggan Village, Kalipucang District, Pangandaran Raise the Sales Value of Sugar Products - Agi Rosyadi; Wilman San Marino; Cindera Syaiful Nugraha; Deny Hidayat (CV. Literasi Indonesia, 2023)
Putrapinggan Village is one of the villages in the Kalipucang District of the Pangandaran Regency with abundant natural resources, and aren sugar is one of the leading products. The very abundant palm sugar potential in the village of Putrapinggan has rather than optimally provided a decent income. Community service is intended to increase the value-added of palm sugar. The method of implementation is exposure and practice. 47 participants were involved in this activity. Activity Evaluation uses a 15-question pre-test and post-test, with the results of the activity increasing partners' knowledge and skills regarding the processing of palm sugar products and motivating and inspiring them to further increase the added value of palm sugar products to improve the welfare of people.